2018
DOI: 10.1186/s12889-018-5984-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of hepatitis B and hepatitis C infections in Northeastern China and the beneficial effect of the vaccination strategy for hepatitis B: a cross-sectional study

Abstract: BackgroundViral hepatitis, mainly hepatitis B and C, is a serious public health problem worldwide. In China, the prevalence of hepatitis B virus (HBV) infection remains high, while that of hepatitis C virus (HCV) infection is controversial. This study investigated the epidemiology of HBV and HCV infections and assessed the beneficial effect of the vaccination strategy for hepatitis B in Northeastern China.MethodsFrom June 2016 to August 2016, 6541 residents of Changchun in Northeastern China were recruited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 25 publications
1
15
1
2
Order By: Relevance
“…Result from this study indicated that HB endemicity level in Malaysia is intermediate 13 . Our study showed that being male was significantly associated with HBsAg seropositivity and similar finding were reported in Brazil and China 22,23 . Our study also found that those who lived in the rural areas had a higher risk of being HBsAg positive.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Result from this study indicated that HB endemicity level in Malaysia is intermediate 13 . Our study showed that being male was significantly associated with HBsAg seropositivity and similar finding were reported in Brazil and China 22,23 . Our study also found that those who lived in the rural areas had a higher risk of being HBsAg positive.…”
Section: Discussionsupporting
confidence: 90%
“…Samples reactive in the HCV screening assay were further tested to determine HCV RNA viral load and genotyping by Cepheid Xpert HCV Viral Load assay and sequencing, respectively 46 , 47 . Detection of HBsAg was considered indicative of chronic HBV infection and detection of anti-HCV was considered a marker of HCV infection 23 .…”
Section: Methodsmentioning
confidence: 99%
“…4,15 In China, genotype C is the predominant HBV genotype in the northeastern region, while genotype B is in the central southern region, genotypes B and C in the southwestern region, and the recombinant genotype C/D in the northwestern region. 16 Therefore, the exact data for the risk factors of CKD in China are needed for the precise management of HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) and hepatitis C (HCV) virus are the most common viruses resulting in chronic liver disease (CLD) [1]. Of the approximately 170 million people worldwide infected with HCV, 71 million progress to have CLD, putting them at risk of cirrhosis and hepatocellular carcinoma (HCC) [2][3]. HCV-associated CLD remains a major indication for liver transplantation [4].…”
Section: Introductionmentioning
confidence: 99%